PENGARUH KOMUNIKASI, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DIVISI PRODUKSI PT. X - HANA FITRIANISA; Surahman Pujianto (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research is to know the effect of communication, motivation and work environment on the employee performance. The form of research used in this research is causality research. The sample used in this research were 62 permanent employees of the production division at PT. X. The sampling method used is a purposive sampling method. Data collection was done by distributing questionnaires. The result of this research is that there is an influence between communication, motivation and work environment on employee performance.